2015
DOI: 10.1186/s12913-015-0687-5
|View full text |Cite
|
Sign up to set email alerts
|

Economic burden of illness associated with diabetic foot ulcers in Canada

Abstract: BackgroundThe primary objective was to estimate the national burden of illness in Canada for diabetic foot ulcer (DFU) for 2011. Secondary objectives included estimating the national incidence and prevalence of DFU, and the 3-year average cost for DFU incident cases.MethodsAnalyses were conducted using four national databases for the period April 1, 2006 to March 31, 2011, with cases being identified by ICD-10 CA codes. Resource utilization and costs, expressed in 2011 Canadian dollars, were estimated for DFU-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(62 citation statements)
references
References 10 publications
2
57
0
3
Order By: Relevance
“…also increases the cost of illness as these patients have to buy drugs for these ailments which also need to be adequately controlled for a successful healing of the diabetic foot ulcer. Hopkins et al found comorbidities to significantly escalate the cost of diabetic foot ulcer in the Canadian study [28]. In a Medicare study in 1995, $3609 per patient per year was spent to treat foot ulcer, 74% of the spending was for inpatient hospital stay, 11.9% for outpatient services, 11.4% homecare and 4% for hospice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…also increases the cost of illness as these patients have to buy drugs for these ailments which also need to be adequately controlled for a successful healing of the diabetic foot ulcer. Hopkins et al found comorbidities to significantly escalate the cost of diabetic foot ulcer in the Canadian study [28]. In a Medicare study in 1995, $3609 per patient per year was spent to treat foot ulcer, 74% of the spending was for inpatient hospital stay, 11.9% for outpatient services, 11.4% homecare and 4% for hospice.…”
Section: Discussionmentioning
confidence: 99%
“…A study done in Europe by van Acker et al found that hospitalization accounted for more than 41% of the total cost of illness [27]. In 2011, in Canada, the resource utilization associated with diabetic foot ulcer for acute institutional care was $3586.6million of which $320.50 million was for admission (89%), $19.1 million for emergency and clinic visits (5%) and an additional $19.0million for interventions [28]. A retrospective pharmacoeconomic study using direct and indirect costs from the perspective of French social security system found that hospitalization represented 70% of the average cost for foot ulcers [29].…”
Section: Discussionmentioning
confidence: 99%
“…These complications are a frequent reason of hospital admission and impose excessive distress and expenses [2][3][4][5][6][7][8]. Diabetic neuropathy and vasculopathy can lead to loss of foot sensation, foot deformities (resulting in pressure points and ulcerations), increased susceptibility to infections (including osteomyelitis), and gangrene.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic wounds due to venous disease are a significant health care burden due to their high incidence, delayed healing and reoccurrence rates . Venous leg ulcers (VLU) occur in 2% of adults over 60 and significant impaired wound healing is a central issue as 24% of VLUs exist longer than a year with a 70% recurrence rate .…”
Section: Introductionmentioning
confidence: 99%